2014
DOI: 10.1186/s12876-014-0224-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of astragalus polysaccharide and β-elemene on LX-2 cell growth, apoptosis and activation

Abstract: BackgroundActivated hepatic stellate cells are the main source of excessive collagen deposition in liver fibrosis. Here we report the inhibitory effects of the combinational treatment of two natural products, astragalus polysaccharide (APS) and β-elemene (ELE) on the activation of human liver hepatic stellate cell line LX-2 cells.MethodsCultured LX-2 cells were treated with different concentrations of APS or ELE for 24 or 48 hours. Cell viability/apoptosis was measured by MTT assay and Annexin V/PI staining , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Currently, the traditional Chinese medicine β-elemene is widely used in the complementary treatment of different types of malignancies [20,21,22,23,24,25,26,27]. β-Elemene has also been found to inhibit the expression of angiotensin II and RhoA/ROCK signaling in hepatic stellate cells and to delay the progression of hepatic fibrosis [28,29,30,31,32]. It may also be effective in antiosteogenic differentiation of ankylosing spondylitis fibroblasts by inhibiting the BMP/SMAD signal pathway and subsequently blocking the expression of ossification marker genes RUNX2 that initiate osteogenic differentiation [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the traditional Chinese medicine β-elemene is widely used in the complementary treatment of different types of malignancies [20,21,22,23,24,25,26,27]. β-Elemene has also been found to inhibit the expression of angiotensin II and RhoA/ROCK signaling in hepatic stellate cells and to delay the progression of hepatic fibrosis [28,29,30,31,32]. It may also be effective in antiosteogenic differentiation of ankylosing spondylitis fibroblasts by inhibiting the BMP/SMAD signal pathway and subsequently blocking the expression of ossification marker genes RUNX2 that initiate osteogenic differentiation [33].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to reverse multidrug resistance [20,21,22,23,24,25,26,27]. In addition, research has shown that β-elemene can inhibit proliferation of human bone fibroblasts and lens epithelial cells and that it can inhibit liver fibrosis [28,29,30,31,32,33,34]. …”
Section: Introductionmentioning
confidence: 99%
“…TGF-β and Col-1 are two important molecules that are secreted by fibroblasts and also induce fibroblasts to promote inflammation and cancer. The TGF-β-induced upregulation of α-SMA and CD44 in LX-2 cells was blocked by βelemene [117]. In addition to CD44, α-SMA is produced when fibroblasts are stimulated and is essential for cell movement, tumor development, and invasion [118,119].…”
Section: β-Elemene Alters Inflammation and Thementioning
confidence: 99%
“…β-Elemene reduces the expression and phosphorylation of Smad3 to inhibit the expression of nuclear transcription factors (such as SNAI1, SNAI2, TWIST, and SIPI1) and block the EMT induced by TGF-β1 in the human breast cancer cell line MCF-7 [116]. TGF-β1 induces the upregulation of α-SMA in human hepatic stellate cells, and its expression and EMT phenotypic transformation can be blocked by β-elemene [117]. TLR4 induces the EMT and the production of antiapoptotic proteins and angiogenesis factors, promoting the survival of cancer cells and inducing immunosuppression [152].…”
Section: β-Elemenementioning
confidence: 99%
“…β-Elemene was found to be effective in inhibiting the viability of fibroblasts cultured from the stiff joints and spines for patients with rheumatoid arthritis [ 9 ] and ankylosing spondylitis [ 10 ], which could slow down the progression of these two diseases. It was also effective in delaying the progression of atherosclerosis [ 11 ] and hepatic fibrosis [ 12 ]. Our previous study also found that β-elemene could effectively inhibit the growth of human airway granulation tissues and fibroblasts cultured from them, which could retard the progression of benign tracheobronchial stenosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%